DESIGN OF ACCOUNTING SYSTEM ON CV. BINTANG LIMA JAYA MANDIRI - Devina Devina; Iskandar Itan (ConCEPt - Conference on Community Engagement Project, 2022)
This activity intends to establish a simple accounting system that can be used by business owners to record and compile proper financial reports. The object of this activity is CV. Bintang Lima Jaya Mandiri, which is engaged in the retail trade in furniture. The Company’s transactions are manually recorded so the business owners struggle in recording transactions because they do not have a more practical and accurate accounting system. From September 6, 2021 to December 31, 2021, a system is being designed to make it easier to record transactions and prepare financial reports. The steps of this community services activities begin with collection of data through use of interviews and observations to understand the Company’s business conditions, flows of the operational activities, and challenges faced by business owners. After which followed by system design and implementation. The result of this activity is an accounting system designed using Microsoft Office Access application, in which business owners can input transactions through forms and can easily access financial reports including statement of financial position and income statement. With the implementation of the accounting system on CV. Bintang Lima Jaya Mandiri, it is expected that business owners will be able to overcome current problems. The recommendation for future researchers is to create a more user-friendly web-based accounting system.